2014
DOI: 10.1371/journal.pone.0111312
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin Disrupts the Development of Streptococcus mutans Biofilms and Facilitates Its Mechanical Removal

Abstract: α-Mangostin (αMG) has been reported to be an effective antimicrobial agent against planktonic cells of Streptococcus mutans, a biofilm-forming and acid-producing cariogenic organism. However, its anti-biofilm activity remains to be determined. We examined whether αMG, a xanthone purified from Garcinia mangostana L grown in Vietnam, disrupts the development, acidogenicity, and/or the mechanical stability of S. mutans biofilms. Treatment regimens simulating those experienced clinically (twice-daily, 60 s exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 67 publications
0
35
0
2
Order By: Relevance
“… Production of acid that damages dental hard tissues ; An agmatine deiminase system and F‐ATPase encoded by the aguBDAC operon and atpD gene , which are major components in acid‐adaptive response that contribute to the aciduric characteristics. The ability to synthesize exopolysaccharides (EPS) from sucrose by the action of multiple glucosyltransferases (Gtfs) encoded by the genes gtfb , gtfc , gtfd , in addition to fructosyltransferase encoded by sacB (ftf ) gene. The glucosyltransferase and fructosyltransferase enzymes catalyse the synthesis of extracellular glucan and fructan polymers from sucrose, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Production of acid that damages dental hard tissues ; An agmatine deiminase system and F‐ATPase encoded by the aguBDAC operon and atpD gene , which are major components in acid‐adaptive response that contribute to the aciduric characteristics. The ability to synthesize exopolysaccharides (EPS) from sucrose by the action of multiple glucosyltransferases (Gtfs) encoded by the genes gtfb , gtfc , gtfd , in addition to fructosyltransferase encoded by sacB (ftf ) gene. The glucosyltransferase and fructosyltransferase enzymes catalyse the synthesis of extracellular glucan and fructan polymers from sucrose, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…(ii) An agmatine deiminase system and F-ATPase encoded by the aguBDAC operon [9] and atpD gene [10], which are major components in acid-adaptive response that contribute to the aciduric characteristics. (iii) The ability to synthesize exopolysaccharides (EPS) from sucrose by the action of multiple glucosyltransferases (Gtfs) encoded by the genes gtfb, gtfc, gtfd, in addition to fructosyltransferase encoded by sacB (ftf) gene.…”
Section: Introductionmentioning
confidence: 99%
“…Since early biofilm establishment by oral streptococci often precedes the attachment of other oral pathogens, inhibiting these biofilms may help prevent further disease (Xiao and Koo, 2010). Anti-biofilm molecules with activity against S. mutans and other oral streptococci include natural products such as alpha-mangostin (Thi et al, 2014), salivary mucin glycoprotein (Frenkel and Ribbeck, 2015), polysaccharide-degrading enzymes (Otsuka et al, 2015), MPC-polymers (Hirota et al, 2011), and small molecules that antagonize glucosyltransferases (Chen et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In the results of that research, amino acids in the chain of the Gtf enzyme were found to be strongly and stably bound with α mangostin, indicating the effects of α mangostin on the Gtf enzyme. 7 Based on the results of the analysis of those treatment groups using mangosteen pericarp extract, it could be seen that this extract at a concentration of 0.78% had greater inhibitory power against the activity of the Gtf enzyme (with a fructose level of 32.63%) than the mangosteen pericarp extract at a concentration of 0.39% (with a fructose level of 49.77%). Nevertheless, the results of the MannWhitney test showed there to be no significant difference between the two treatment groups.…”
Section: Discussionmentioning
confidence: 98%
“…However, the main one is GtfB because it can catalyze the formation of insoluble, alfa-linked glucan. 7 Inhibition of enzyme activity is also known to be caused by tannin which has an inhibitory power of 31.39%. 8 In addition, flavonoids also actively limit the activity of the Gtf enzyme as well as promoting antibacterial activity.…”
mentioning
confidence: 99%